β-Dispersion of blood during sedimentation - Ahmet C. Sabuncu (Nature Portfolio, 2021)
Abstract Aggregation of human red blood cells (RBC) is central to various pathological conditions from bacterial infections to cancer. When left at low shear conditions or at hemostasis, RBCs form aggregates, which resemble stacks of coins, known as ‘rouleaux’. We experimentally examined the interfacial dielectric dispersion of aggregating RBCs. Hetastarch, an RBC aggregation agent, is used to mimic conditions leading to aggregation. Hetastrach concentration is incrementally increased in blood from healthy donors to measure the sensitivity of the technique. Time lapse electrical impedance measurements were conducted as red blood cells form rouleaux and sediment in a PDMS chamber. Theoretical modeling was used for obtaining complex permittivity of an effective single red blood cell aggregate at various concentrations of hetastarch. Time response of red blood cells’ impedance was also studied to parametrize the time evolution of impedance data. Single aggregate permittivity at the onset of aggregation, evolution of interfacial dispersion parameters, and sedimentation kinetics allowed us to distinguish differential aggregation in blood.